Logistic equations in tumour growth modelling - Marciniak-Czochra, Anna (Applied mathematics and computer science, 2003)
The aim of this paper is to present some approaches to tumour growth modelling using the logistic equation. As a first approach a well-known ordinary differential equation is used to model the Ehrlich ascities tumour in mice. For the same kind of tumour, a logistic equation with time delay is also used. As the second approach, a logistic equation with diffusion is proposed. In this case a delay argument in the reaction term is also considered. Some mathematical properties of the presented models are studied in the paper. The results are illustrated using computer simulations.